Comprehensive assessment of the indoor air quality in a chlorinated Olympic-size swimming pool. (March 2020) - Felgueiras, Fátima; Mourão, Zenaida; Morais, Catarina; Santos, Hugo; Gabriel, Marta Fonseca; de Oliveira Fernandes, Eduardo
Highlights: Passive and active sampling of air THM resulted in non-correlated data. Besides DBP, other harmful VOC and UFP can constitute a concern in swimming pools. Breathing zones of elite swimmers, coaches and staff presented different THM levels. Air THM concentrations reveled a relevant seasonal and intra-day variation. CO2, CO and water-related factors were predictors of air THM and non-THM VOC levels. Abstract: Elite swimmers and swimming pool employees are likely to be at greater health risk due to their regular and intense exposure to air stressors in the indoor swimming pool environment. Since data on the real long-term exposure is limited, a long-term monitoring and sampling plan (22 non-consecutive days, from March to July 2017) was carried out in an indoor Olympic-size pool with a chlorine-based disinfection method to characterize indoor environments to which people involved in elite swimming and maintenance staff may be exposed to. A comprehensive set of parameters related with comfort and environmental conditions (temperature, relative humidity (RH), carbon dioxide (CO2 ) and monoxide and ultrafine particles (UFP)) were monitored both indoors and outdoors in order to determine indoor-to-outdoor (I/O) ratios. Additionally, an analysis of volatile organic compounds (VOC) concentration and its dynamics was implemented in three 1-hr periods: early morning, evening elite swimmers training session and late evening. Samplings were simultaneously carried out in the air layer above the water surface and in the air surrounding the pool, selected to be representative of swimmers and coaches/employees' breathing zones, respectively. The results of this work showed that the indoor climate was very stable in terms of air temperature, RH and CO2 . In terms of the other measured parameters, mean indoor UFP number concentrations (5158 pt/cm 3 ) were about 50% of those measured outdoors whereas chloroform was the predominant substance detected in all samples collected indoors (13.0–369.3 µg/m 3 ), among a varied list of chemical compounds. An I/O non-trihalomethanes (THM) VOC concentration ratio of 2.7 was also found, suggesting that, beyond THM, other potentially hazardous VOC have also their source(s) indoors. THM and non-THM VOC concentration were found to increase consistently during the evening training session and exhibited a significant seasonal pattern. Compared to their coaches, elite swimmers seemed to be exposed via inhalation to significantly higher total THM levels, but to similar concentrations of non-THM VOC, during routine training activities. Regarding swimming employees, the exposure to THM and other VOC appeared to be significantly minimized during the early morning period. The air/water temperature ratio and RH were identified as important parameters that are likely to trigger the transfer processes of volatile substances from water to air and of their accumulation in the indoor environment of the swimming pool, respectively.